The Relationship between Cognitive Ability and Risk Preferences in a Developing Nation: Findings from the Field - Ali Moghaddasi Kelishomi; Daniel Sgroi (Institute of Labor Economics (IZA), 2022)
We find a strong relationship between risk-loving preferences and cognitive ability which becomes stronger as adherence to the generalized axiom of revealed preference (a proxy for rationality) increases. Our results are taken from a field study of individuals at the very bottom of the income distribution in a developing nation. Our results for some of the poorest in the world support recent findings drawn from subjects in wealthy Western nations, suggesting there may be a stable relationship between risk preferences and cognitive ability for the human population as a whole irrespective of socio-economic status.
Keywords: I11; I12; I18; C93; D03; 330; risk; cognitive ability; rationality; generalized axiom of revealed preference; field experiment; low incomes; developing nation